SUN-605 A Case of Metastatic Papillary Thyroid Cancer Presenting as a Skin Lesion - Brown, Teresa (J Endocr Soc, 2019)
Introduction: The most common sites of thyroid cancer metastases include the lymph nodes, lungs, bone, and occasionally the brain. Skin metastases are rare and the most common location that has been reported is the scalp (1-3). When they do occur, skin metastases usually occur in the setting of locally invasive thyroid cancer or widely disseminated neoplastic disease (4). Case: A 69 year old male with a history of coronary artery disease and thyroid surgery (done for an unknown, benign condition, as per patient) presented to our dermatology clinic with an exophytic, violaceous skin lesion (1 x 0.5 cm) below his left clavicle. He noticed the lesion 3 years ago and noted that it had enlarged over the 3 months prior to presentation. An excisional biopsy of the lesion was consistent with papillary thyroid carcinoma positive for TTF, CK7, and thyroglobulin. The patient was subsequently evaluated in our endocrine clinic at which time a thyroid ultrasound revealed a 4 mm right thyroid nodule and confirmed prior history of a left hemithyroidectomy. He underwent completion thyroidectomy and radioactive iodine ablation therapy with 80 mci of I-131. Surgical pathology showed no carcinoma of the right thyroid lobe. A post-RAI whole body scan demonstrated no evidence of metastatic disease and a neck ultrasound did not reveal any thyroid remnant tissue or abnormal lymph nodes. An initial pre-operative Tg level was 31.5 ng/ml that decreased to 3.2 ng/ml five months post-RAI. The Tg Ab remains undetectable. Currently, he is without structural evidence of disease. We have recommended a TSH goal of less than 0.5 uIU/mL and plan to monitor the Tg levels with a 1 year follow-up whole body scan. Conclusion: We present an unusual case of metastatic papillary thyroid cancer manifesting as a dermatologic lesion in the absence of local concurrent or advanced metastatic disease. It is important to consider thyroid carcinoma in the differential diagnosis of atypical skin lesions. References 1. Farina, Eleonora, et al. "Unusual thyroid carcinoma metastases: a case series and literature review." Endocrine pathology 27.1 (2016): 55-64. 2. Alwaheeb, S., et al. "Cutaneous manifestations of thyroid cancer: a report of four cases and review of the literature." Journal of clinical pathology 57.4 (2004): 435-438. 3. Avram, Anca M., et al. "Choroidal and skin metastases from papillary thyroid cancer: case and a review of the literature." The Journal of Clinical Endocrinology & Metabolism 89.11 (2004): 5303-5307. 4. Dahl, Patrick R., et al. "Thyroid carcinoma metastatic to the skin: a cutaneous manifestation of a widely disseminated malignancy." Journal of the American Academy of Dermatology 36.4 (1997): 531-537.